A NEW SYRINGOTHYRIDID GENUS (SPIRIFERINIDA, BRACHIOPODA) FROM THE EARLY PERMIAN OF INTERIOR OMAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
Representatives of the Syringothyrididae (Spiriferinida) are a significant component of the Early Permian brachiopod faunas, even if usually subordinate in number of specimens, except for the Interior of Oman, where they dominate the faunal assemblage. A new genus Pachycyrtella - with type-species P. omanensis n. sp. - is here established in order to include gondawanan species - previously assigned to the genus Cyrtella - characterized by high and apsacline to orthocline ventral interarea, thick umbo and deep dorsal median furrow.